Ағылшын тілі сабағында жаңа технологияларды пайдаланудың тиімділігі - Габдешева, А.Е.; Иргалиева, Г.Х. (My University, 2016)
All processes of learning: the creation and development of scientific and studied cognitive performance. Improvement of English language training. Psycho-pedagogical views. Psycho-pedagogical objective the training and education of our children with the use of new information technologies and the development of techniques used in the classroom.
Keywords: internet; software; information technology; interactive whiteboards; computer training